Organellar Genome Variation and Genetic Diversity of Chinese Pyropia yezoensis - Xu, Kuipeng; Yu, Xinzi; Tang, Xianghai; Kong, Fanna; Mao, Yunxiang (Frontiers in Marine Science, 2019)
Pyropia yezoensis is an economically important marine algae crop that, due to its large economic value, has generated considerable interest in the development of breeding programs to improve its production rates. Here, we sequenced the complete mitochondrial and plastid genomes of the P. yezoensis strain RZ-58 using PacBio RS II sequencing technology. The mitochondrial genome (mtDNA) is 41,692 bp in size with an overall GC content of 32.72%, and the plastid genome (ptDNA) is 191,977 bp with a GC content of 33.09%. The complete mitochondrial and plastid genomes of 53 individuals from 3 geographical populations were then resequenced using NGS technology to characterize their molecular features. When compared, the plastid genomes displayed similar genomic lengths and conserved gene synteny. However, mitochondrial genomes were quite different in length, which was mainly due to the different patterns of intron distributions. Single nucleotide polymorphisms (SNPs) were examined to evaluate the genetic diversity of different geographical populations. High diversity was observed across the whole collection with moderate genetic variation between populations. In total, there were 463 and 366 high-quality SNPs detected in the mtDNA and ptDNA, respectively. The Qingdao wild group has the highest diversity with a mean pi of 0.00348 for mtDNA and 0.000388 for ptDNA, while the Yantai group had the lowest diversity. Cluster based grouping and principal component analysis revealed three subpopulations in the whole collections. However, a genetic break of organellar DNA was observed in populations at sympatric localities, which was inferred as the result of historic biogeographic events. Our findings provide important information to guide the marker-assisted selective breeding of Chinese P. yezoensis in the future.